2015
DOI: 10.1016/j.physio.2015.03.3438
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of conceptual frameworks to knowledge translation interventions in physical therapy

Abstract: -J. et Hunt, M. (2015). The contribution of conceptual frameworks to knowledge translation interventions in physical therapy. Physical therapy, 95(4), 630-639.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It may also help to map existing literature and other researchers' points of view and observations on HIV stigma reduction that would help situate new studies in terms of previous works (Armstrong, Hall, Doyle, & Waters, 2011). Moreover, our conceptual framework can be used to (a) identify and assess how particular variables connect with each other to form a mechanism, (b) examine the relative strength of the potential mechanisms, and, (c) most importantly, serve as a reference point to interpret findings (Hudon et al, 2015;Triana, 2008).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
See 2 more Smart Citations
“…It may also help to map existing literature and other researchers' points of view and observations on HIV stigma reduction that would help situate new studies in terms of previous works (Armstrong, Hall, Doyle, & Waters, 2011). Moreover, our conceptual framework can be used to (a) identify and assess how particular variables connect with each other to form a mechanism, (b) examine the relative strength of the potential mechanisms, and, (c) most importantly, serve as a reference point to interpret findings (Hudon et al, 2015;Triana, 2008).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
“…A conceptual framework not only increases understanding of contextual factors that may mediate or moderate intervention outcomes, it also guides future research projects and facilitates the development and implementation of robust interventions (Hudon, Gervais, & Hunt, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that the different ways that theory is applied in implementation research can be organised in five categories: 1) as a general philosophical framework for the research; 2) as a guide to select educational strategies; 3) as a way of identifying variables for correlation or prediction; 4) as a way of identifying variables to measure implementation effectiveness; and 5) as a guide or framework to qualitative study design and/or analysis [68]. Also in rehabilitation, there is growing recognition of the importance of implementation activities to ensure that research findings are integrated into clinical practice, of implementation research to evaluate implementation efforts, and of the use of theory in implementation interventions [68,69]. The use of a conceptual framework to guide the design of implementation interventions has particularly been advocated.…”
Section: Diffusion ("Let It Happen")mentioning
confidence: 99%
“…In their systematic review of KT interventions used among rehabilitation professionals, Jones et al reported that active, multi-component KT interventions (i.e., educational meetings, summarized materials) were the most eff ective at improving physiotherapists' knowledge and practice. 5 Moreover, Hudon et al proposed the value of conceptual frameworks to guide the implementation of KT interventions, 6 and the knowledge-to-action framework addressed the most barriers to EBP implementation reported by physiotherapists. 7 CAF physiotherapists have reported some discrepancies from EBP in their management of LAS, including the frequent use of electrotherapy modalities, a limited prescription of balance and strengthening interventions, and limited use of balance and functional performance outcome measures.…”
Section: Introductionmentioning
confidence: 99%